2014
DOI: 10.1146/annurev-genet-120213-092314
|View full text |Cite
|
Sign up to set email alerts
|

Cancer: Evolution Within a Lifetime

Abstract: Subclonal cancer populations change spatially and temporally during the disease course. Studies are revealing branched evolutionary cancer growth with low-frequency driver events present in subpopulations of cells, providing escape mechanisms for targeted therapeutic approaches. Despite such complexity, evidence is emerging for parallel evolution of subclones, mediated through distinct somatic events converging on the same gene, signal transduction pathway, or protein complex in different subclones within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 147 publications
9
133
0
1
Order By: Relevance
“…Such a dichotomy has been framed in the context of micro-versus macro-evolution, with gradual accumulation of point mutations (micro-evolution) presented in opposition to a saltationist view, which emphasizes the importance of largescale chromosomal alterations and bursts of mutations (macro-evolution) (Gerlinger et al, 2014b). …”
Section: Gradualism Versus Punctuated Evolutionmentioning
confidence: 99%
“…Such a dichotomy has been framed in the context of micro-versus macro-evolution, with gradual accumulation of point mutations (micro-evolution) presented in opposition to a saltationist view, which emphasizes the importance of largescale chromosomal alterations and bursts of mutations (macro-evolution) (Gerlinger et al, 2014b). …”
Section: Gradualism Versus Punctuated Evolutionmentioning
confidence: 99%
“…The synergy provided by combining H90Ins with KIs is predicted to reduce the evolutionary space available to cancer by simultaneously targeting cellular proteostasis and multiple pro-growth and metastatic signaling pathways (Rutherford and Lindquist 1998); (Workman et al 2007a;Gerlinger et al 2014); (Whitesell et al 2014). This hypothesis is further supported by recent observations that HSP90 influences the function of a number of other signaling components that are overexpressed, or otherwise deregulated in cancer, including transcription factors, E3-ligases, metabolic enzymes, and protein translational machinery (Taipale et al 2014); (Liu et al 2015); (Solier et al 2012); (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, the anarchic proliferation that characterizes within-host cancer evolution commonly includes a high diversity of aneuploid cell lineages associated with disease progression, and at least some of these are thought to arise via chromosome missegregation from tetraploid intermediates (for review, see Davoli and de Lange 2011;Burrell and Swanton 2014;Gerlinger et al 2014b). Tetraploid intermediates may be quite common and have been suggested to occur in >50% of liver adenocarcinomas and āˆ¼30% of pancreas and lung adenocarcinomas, cervical carcinomas, neuroblastomas, and Hodgkin's lymphomas (see references in Davoli and de Lange 2011).…”
Section: Mammalsmentioning
confidence: 99%
“…This is no surprise given the range of evolutionary trajectories that characterize diverse cancer types and the difficulty of obtaining a truly representative picture of the evolutionary paths that cell lineages follow within a single tumor (Gerlinger et al 2014b;Walther et al 2015). Beyond the unresolved population genetic considerations of the effects of variation in a polyploid context (e.g., see Otto and Whitton 2000;Gerstein and Otto 2009), on the phenotypic side, recent work suggested that polyploidy may indeed promote rampant aneuploidy and genetic and phenotypic diversity (Lagadec et al 2012;Erenpreisa and Cragg 2013;Zhang et al 2013).…”
Section: Mammalsmentioning
confidence: 99%